Prevalência de parto pré-termo eletivo e suas principais repercussões neonatais em hospital de referência na cidade de Belém¬ Pa. - SOUSA, Ana Cristina Cardoso de (2023)
Objective: To study the prevalence of elective preterm deliveries occurred in the Fundação Santa Casa de Misericórdia do Pará (FSCMPA) hospital in the year 2010, and know its main neonatal repercussions. Methodology: A epidemiological study, cross sectional, of collect and descriptive, of 108 cases of female patients, pregnant with one fetus, alive, absent of malformations, with gestational age (GA) greater than 20 and less than 37 weeks gestation who were admitted in wards medium (ward Santa Marta) and high risks of clinical tocogynecology FSCMPA hospital in the period from 1 January 2010 to 1 January 2011, who had an indication for early delivery because to some complications maternal and/or fetus. Results: Most patients were age group between 20 and 30 years of age (53.7%) and were single (60.2%); in relation to education, 38.9% hadn’t completed elementary school and 64.8% were students or working on their own house. The personal history, 30.8% had hypertension and, among obstetric history, 45.8% had previous pregnancies, 37.3% had given birth and 16.9% had history of abortion. Of the previous pregnancies, 11.0% were preterm births. Of the complications in previous pregnancies, abortion resulted for 48.8% of cases, and preeclampsia and eclampsia by 14,8% and 9,7%, respectively, and, preeclampsia, with 42,8% and eclampsia, with 28,6% were the main reasons that indicated preterm delivery. In relation to current pregnancy, only 31.7% had received prenatal care with six or more visits; prevailed as maternal complications, vaginal fluid loss and vaginal bleeding (18.8% and 18.0%, respectively), and the main reason for maternal indication of preterm delivery was preeclampsia, with 32.0%, and fetal acute fetal distress with 61.5% of cases. Most newborns were male (58.3%), most classified as underweight (64.8%), borderline premature (57.4%, 7.4% were very preterm extreme) and as small for gestational age (52.8%). Of the neonatal complications, the respiratory totaled 92.9% of cases. Conclusion: The occurrence of preterm birth remains a big public health problem, especially when occurs the lack of demand and lack of prenatal care, which has drastic consequences for pregnant women, newborn and later to child, these problems could be minimized if a health politic to both, mother and child, were most appropriate, with the dissemination of preventive and educational measures, with the best qualified medical professionals and the best structure of health services aiming efficient provision service.